Financial Accounting Standards for Micro, Small & Medium Entities (SAK EMKM) Implementation and Factors That Affect It - Nur Diana Adhikara (University of Islam Malang, 2018)
The low understanding of accounting and financial accounting standards is a fundamental problem for Micro, Small & Medium Enterprises (MSMEs) in Indonesia. This makes it difficult to prepare and manage financial statements. The presence of the Financial Accounting Standards for Non-Publicly-Accountable Entities (SAK-ETAP) on January 1, 2011, is expected to accommodate small and medium enterprises in making easy, transparent and accountable financial statements. But In fact, many MSMEs that have not been able to apply SAK ETAP properly because it is considered to be too complex and not by the financial reporting needs of MSMEs. On January 1, 2018, SAK EMKM was enacted as a standard that could help about 57.9 million MSME entrepreneurs in Indonesia in properly preparing their financial statements without having to get caught up in the complexity of it. SAK EMKM is a much simpler financial accounting standard than SAK ETAP. This study aims to provide empirical evidence on the perception of MSME business actors regarding the importance of financial bookkeeping and reporting for their business and the factors that affect the level of understanding of MSME’s related to SAK EMKM. The sample of research was MSMEs business actors in Malang Raya with purposive sampling method with the total of 225 respondents. The results showed that company size, educational background, and level of education affect the MSME business entrepreneurs' perception of the importance of financial bookkeeping and reporting. While the level of understanding of MSME business entrepreneurs of SAK EMKM is affected by the level of information on SAK EMKM, educational background and education level of the MSME business actors.